1998
DOI: 10.1536/ihj.39.681
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Diagnosis of a Family with Hypercholesterolemia by a Mismatched PCR-RFLP Method for Genotyping Single Base Substitution of the LDL Receptor Gene.

Abstract: Plasma lipid and lipoprotein levels reflect in part the influence of relevant genetic loci. Defects at some of these loci account for specific types of dyslipoproteinemia occurring with regularity among family members. In the course of familial investigations of coronary artery disease, we identified an family in which several members were affected with elevated low density lipoprotein (LDL) cholesterol levels. To study the genetic defects responsible for plasma lipoprotein abnormality in this pedigree, we dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This polymorphism was first described as a SSCP variant which was very difficult to type [19]. Then, Yamaki et al [20] developed a mismatched RFLP method for the typing of LDLR G1413A. However, in the present study, we successfully typed this SNP by CE-SSCP analysis.…”
Section: Accuracy and Precision Of Multicolor Fluorescent Sscp Analysmentioning
confidence: 64%
“…This polymorphism was first described as a SSCP variant which was very difficult to type [19]. Then, Yamaki et al [20] developed a mismatched RFLP method for the typing of LDLR G1413A. However, in the present study, we successfully typed this SNP by CE-SSCP analysis.…”
Section: Accuracy and Precision Of Multicolor Fluorescent Sscp Analysmentioning
confidence: 64%
“…However, it has been shown that the G allele of this SNP cosegregated with elevated LDL cholesterol without exception in a Japanese pedigree. 35 The silent change in exon 12 has been shown to be associated with altered concentrations of total and LDL cholesterol in FH studies. 31,33 Another study showed that this SNP was associated with obesity overall, but not with plasma lipid levels.…”
Section: Discussionmentioning
confidence: 99%